PERANCANGAN APLIKASI PENENTUAN KELAS UNGGULAN MENGGUNAKAN METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) STUDI : KASUS SEKOLAH DASAR 7 TANGERANG SELATAN - Derry Bagus Muharto; Niki Ratama (Journal of Research and Publication Innovation, 2024)
In the selection of outstanding students at SDN 7 Tangerang Selatan using as an assessment material so that the selection seems subjective while there are still many other determining factors that can be considered in selecting superior classes. This subjective selection has an impact on parties who feel disadvantaged because the selection is considered less transparent. Therefore, a decision support system is needed that reduces subjectivity in the selection so that it can help schools in conducting transparent selections. By using the SMART Method (Simple Multi Attribute Technique) is one of the decision-making methods that can add up the performance weights of each different object and have the same opportunity. In the decision-making process for selecting superior classes at SDN 7 Tangerang Selatan, several criteria are needed to help in decision making, and each criterion has its own weight of importance to determine alternatives. The best of the many students in the class. By creating this decision support system, it is hoped that it will be able to provide a transparent assessment and can determine the best selection alternative useful for assisting in the selection at SDN 7 Tangerang Selatan